Anterior uveal neurilemmoma–a rare neoplasm simulating malignant melanoma. Issue 1 (January 1987) - Smith, P A; Damato, B E; Ko, M K; Lyness, R W
Abstract : A 30-year-old woman presented with dilated episcleral vessels in the right eye which were found to be associated with an underlying ciliary body tumour. Contact lens examination, transpupillary transillumination, ultrasonography, computerised tomography, magnetic resonance imaging, and fine needle aspiration biopsy produced apparently conflicting and inconclusive results, and the eye was enucleated. Light and electron microscopy showed the lesion to be a neurilemmoma (schwannoma), of which very few cases have been reported. The clinical and pathological features are described and discussed.